2022
DOI: 10.1177/14759217221088492
|View full text |Cite
|
Sign up to set email alerts
|

Looseness monitoring of multiple M1 bolt joints using multivariate intrinsic multiscale entropy analysis and Lorentz signal-enhanced piezoelectric active sensing

Abstract: Bolts are widely used in the fields of mechanical, civil, and aerospace engineering. The condition of bolt joints has a significant impact on the safe and reliable operation of the whole equipment. The failure of bolt joints monitoring leads to severe accidents or even casualties. This paper proposes a novel bolt joints monitoring method using multivariate intrinsic multiscale entropy (MIME) analysis and Lorentz signal-enhanced piezoelectric active sensing. Lorentz signal is used as excitation signal in piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Thus, the triaxial accelerometer signals are analyzed in our paper with the aim of achieving accurate tool wear monitoring. The studies showed that the dynamic properties of the signal can be accurately described by BLIMFs [47][48][49]. Thus, multiscale entropy analysis by extracting features of BLIMFs can be used to detect the health conditions of complex dynamic systems.…”
Section: The Proposed In-situ Tool Wear Monitoring Approach Using Mul...mentioning
confidence: 99%
“…Thus, the triaxial accelerometer signals are analyzed in our paper with the aim of achieving accurate tool wear monitoring. The studies showed that the dynamic properties of the signal can be accurately described by BLIMFs [47][48][49]. Thus, multiscale entropy analysis by extracting features of BLIMFs can be used to detect the health conditions of complex dynamic systems.…”
Section: The Proposed In-situ Tool Wear Monitoring Approach Using Mul...mentioning
confidence: 99%
“…MVMD is able to obtain more accurate BLIMFs, which can effectively alleviate the mode aliasing problem. Based on the above advantages, MVMD can provide a new way to process multivariate signals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the developments in convolutional neural networks (CNN) over recent years, classical CNN models such as the ResNeXt [ 1 ], Dual Path Networks [ 2 ], and EfficientNet [ 3 ] have been proposed, which has been proven to possess good image recognition abilities. Consequently, it is great for researchers to continue working toward importing CNN models into inspection applications and obtain good results, such as for industrial inspection [ 4 , 5 ], cryo-electron tomogram classification [ 6 ], lithium-ion battery electrode defect detection [ 7 ], solar cell surface defect inspection [ 8 ], bolt joints monitoring [ 9 ] and rolling bearing robust fault diagnosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%